MARS/NDRI/KSU Communications Workshop: Part 7D. Communication Strategy, Tools, and Lessons from the Aflasafe Initiative - Ortega-Beltran, Alejandro; Bandyopadhyay, Ranajit (My University, 2022)
The International Institute of Tropical Agriculture (IITA) is a non‐profit institution that generates agricultural innovations to meet Africa’s most pressing challenges of hunger, malnutrition, poverty, and natural resource degradation. Working with various partners across sub‐Saharan Africa, we improve livelihoods, enhance food and nutrition security, increase employment, and preserve natural resource integrity.
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication